Evidence for intergranular tunnelling in polyaniline passivated alpha-Fe nanoparticles - Sunny, Vijutha; Narayanan, T. N.; Sajeev, U. S.; Joy, Pattayil Alias; Kumar, D. Sakthi; Yoshida, Yasuhiko; Anantharaman, Maliemadom R. (Nanotechnology, 2006)
Nanoparticles are of immense importance both from the fundamental and application points of view. They exhibit quantum size effects which are manifested in their improved magnetic and electric properties. Mechanical attrition by high energy ball milling (HEBM) is a top down process for producing fine particles. However, fineness is associated with high surface area and hence is prone to oxidation which has a detrimental effect on the useful properties of these materials. Passivation of nanoparticles is known to inhibit surface oxidation. At the same time, coating polymer film on inorganic materials modifies the surface properties drastically. In this work a modified set-up consisting of an RF plasma polymerization technique is employed to coat a thin layer of a polymer film on Fe nanoparticles produced by HEBM. Ball-milled particles having different particle size ranges are coated with polyaniline. Their electrical properties are investigated by measuring the dc conductivity in the temperature range 10-300 K. The low temperature dc conductivity (I-V) exhibited nonlinearity. This nonlinearity observed is explained on the basis of the critical path model. There is clear-cut evidence for the occurrence of intergranular tunnelling. The results are presented here in this paper.

Optically transparent magnetic nanocomposites based on encapsulated Fe3O4 nanoparticles in a sol-gel silica network - Thomas, Senoy; Sakthikumar, D.; Joy, Pattayil Alias; Yoshida, Yasuhiko; Anantharaman, Maliemadom R. (Nanotechnology, 2006)
Composite Fe3O4-SiO2 materials were prepared by the sol-gel method with tetraethoxysilane and aqueous-based Fe3O4 ferrofluids as precursors. The monoliths obtained were crack free and showed both optical and magnetic properties. The structural properties were determined by infrared spectroscopy, x-ray diffractometry and transmission electron microscopy. Fe3O4 particles of 20 nm size lie within the pores of the matrix without any strong Si-O-Fe bonding. The well established silica network provides effective confinement to these nanoparticles. The composites were transparent in the 600-800 nm regime and the field dependent magnetization curves suggest that the composite exhibits superparamagnetic characteristics.

Impact of zinc substitution on the structural and magnetic properties of chemically derived nanosized manganese zinc mixed ferrites - Gopalan, E. Veena; Al-Omari, I. A.; Malini, K. A.; Joy, Pattayil Alias; Kumar, D. Sakthi; Yoshida, Yasuhiko; Anantharaman, Maliemadom R. (Journal of Magnetism and Magnetic Materials, 2009)
Mn(1-x)Zn(x)Fe(2)O(4) nanoparticles (x = 0-1) were synthesized by wet chemical co-precipitation techniques. X-ray diffraction, transmission electron microscopy and high-resolution transmission electron microscopy were effectively utilized to investigate the different structural parameters. The elemental analysis was conducted using energy-dispersive spectrum and inductively coupled plasma analysis. The magnetic properties such as magnetization and coercivity were measured using vibrating sample magnetometer. The observed magnetization values of the nanoparticles were found to be lower compared to the bulk counterpart. The magnetization showed a gradual decrease with zinc substitution except for a small increase from x = 0.2 to 0.3. The Curie temperature was found to be enhanced in the case of ferrites in the nanoregime. The variation in lattice constant, reduced magnetization values, variation of magnetization with zinc substitution, the presence of a net magnetic moment for the zinc ferrite and the enhancement in Curie temperature in Mn(1-x)Zn(x)Fe(2)O(4) all provide evidence to the existence of a metastable cation distribution together with possible surface effects at the nanoregime. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Manganese zinc ferrite

On the structural, magnetic and electrical properties of sol-gel derived nanosized cobalt ferrite - Gopalan, E. Veena; Joy, Pattayil Alias; Al-Omari, I. A.; Kumar, D. Sakthi; Yoshida, Yasuhiko; Anantharaman, Maliemadom R. (Journal of Alloys and Compounds, 2009)
Nanoparticles of cobalt ferrite were synthesized by sol gel method. These particles were structurally characterized by using X-Ray Diffraction and Transmission Electron Microscopy, High Resolution Transmission Electron Microscopy, Energy Dispersive Spectrum and Inductively Coupled Plasma Analysis and the results confirmed the formation of spherically shaped nanoparticles of cobalt ferrite having a size lying in the range of 13-14 nm. The as prepared sample was sintered at 800 degrees C and the structural, magnetic and dielectric properties were measured. The dielectric properties were studied and analyzed as a function of temperature and frequency. The ac and dc conductivity studies were carried out to delve into the conduction mechanism. The existing models based on quantum mechanical tunneling were effectively employed to explain the frequency dependent conductivity. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Electronic Transport; Magnetic measurements; Magnetically ordered materials; Nanostructures; Scanning and transmission electron microscopy; Sol-gel synthesis; X-ray diffraction

Inverse magnetocaloric effect in sol-gel derived nanosized cobalt ferrite - Gopalan, E. Veena; Al-Omari, I. A.; Kumar, D. Sakthi; Yoshida, Yasuhiko; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Applied Physics A-Materials Science & Processing, 2010)
The magnetocaloric properties of cobalt ferrite nanoparticles were investigated to evaluate the potential of these materials as magnetic refrigerants. Nanosized cobalt ferrites were synthesized by the method of sol-gel combustion. The nanoparticles were found to be spherical with an average crystallite size of 14 nm. The magnetic entropy change (Delta S (m)) calculated indirectly from magnetization isotherms in the temperature region 170-320 K was found to be negative, signifying an inverse magnetocaloric effect in the nanoparticles. The magnitudes of the Delta S (m) values were found to be larger when compared to the reported values in the literature for the corresponding ferrite materials in the nanoregime.

Synthesis of bio-compatible SPION-based aqueous ferrofluids and evaluation of radiofrequency power loss for magnetic hyperthermia - Mary, Antony P. Reena; Narayanan, T. N.; Sunny, Vijutha; Sakthikumar, D.; Yoshida, Yasuhiko; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Nanoscale Research Letters, 2010)
Bio-compatible magnetic fluids having high saturation magnetization find immense applications in various biomedical fields. Aqueous ferrofluids of superparamagnetic iron oxide nanoparticles with narrow size distribution, high shelf life and good stability is realized by controlled chemical co-precipitation process. The crystal structure is verified by X-ray diffraction technique. Particle sizes are evaluated by employing Transmission electron microscopy. Room temperature and low-temperature magnetic measurements were carried out with Superconducting Quantum Interference Device. The fluid exhibits good magnetic response even at very high dilution (6.28 mg/cc). This is an advantage for biomedical applications, since only a small amount of iron is to be metabolised by body organs. Magnetic field induced transmission measurements carried out at photon energy of diode laser (670 nm) exhibited excellent linear dichroism. Based on the structural and magnetic measurements, the power loss for the magnetic nanoparticles under study is evaluated over a range of radiofrequencies.
Keywords: Magnetic heating; Magnetic hyperthermia; Magnetic relaxation; Power loss; Superparamagnetism

Template-assisted synthesis and characterization of passivated nickel nanoparticles - Gopalan, E. Veena; Malini, K. A.; Santhoshkumar, G.; Narayanan, T. N.; Joy, Pattayil Alias; Al-Omari, I. A.; Kumar, D. Sakthi; Yoshida, Yasuhiko; Anantharaman, Maliemadom R. (Nanoscale Research Letters, 2010)
Potential applications of nickel nanoparticles demand the synthesis of self-protected nickel nanoparticles by different synthesis techniques. A novel and simple technique for the synthesis of self-protected nickel nanoparticles is realized by the inter-matrix synthesis of nickel nanoparticles by cation exchange reduction in two types of resins. Two different polymer templates namely strongly acidic cation exchange resins and weakly acidic cation exchange resins provided with cation exchange sites which can anchor metal cations by the ion exchange process are used. The nickel ions which are held at the cation exchange sites by ion fixation can be subsequently reduced to metal nanoparticles by using sodium borohydride as the reducing agent. The composites are cycled repeating the loading reduction cycle involved in the synthesis procedure. X-Ray Diffraction, Scanning Electron Microscopy, Transmission Electron microscopy, Energy Dispersive Spectrum, and Inductively Coupled Plasma Analysis are effectively utilized to investigate the different structural characteristics of the nanocomposites. The hysteresis loop parameters namely saturation magnetization and coercivity are measured using Vibrating Sample Magnetometer. The thermomagnetization study is also conducted to evaluate the Curie temperature values of the composites. The effect of cycling on the structural and magnetic characteristics of the two composites are dealt in detail. A comparison between the different characteristics of the two nanocomposites is also provided.
Keywords: Nickel nanoparticles; Polymer-metal nanocomposites; Strongly acidic cation exchange resin; Stuctural and magnetic properties; Weakly acidic cation exchange resin